POLA KOMUNIKASI ORGANISASI SATUAN POLISI PAMONG PRAJA DALAM MENJAGA KETENTRAMAN DAN KETERTIBAN PEDAGANG KAKI LIMA DI DKI JAKARTA (Studi Deskriptif pada Satuan Polisi Pamong Praja Pemerintah Provinsi DKI Jakarta di Jakarta Pusat) - KRISTANTY, SHINTA; LUBIS, ARMAINI (Communication, 2013)
The main duty of Satpol PP (The Municipal Police - Civil Service Police Unit) is to regulate and maintain the security of the community, but in reality municipal police organization holds its bad image toward the community, this bad image is more attached to the municipal police officers themselves. On this basis, the study aims to describe the patterns of communication within the body of Satpol PP organizations, particularly in Central Jakarta. This is because of Central Jakarta is one of the strategic area for street vendors to sell their goods. Moreover, the location is near from National Monument as a center of tourism destination for local or foreign tourists. The formulation of research problems is how the communication patterns of Satpol PP organizations in curbing the cadger in Central Jakarta. The research applies the organizational communication theory of Human Relations School, and includes the concept of organizational communication patterns such as message flow in the organization, communication network, organizational communication atmosphere and organizational leadership patterns. The method of research used is a case study with a qualitative approach. The results show that the Satpol PP organization in DKI Jakarta (central Jakarta) style has persuasive and informative communication, the message flow is in one direction and in both directions between the leaders and the officers of the Satpol PP, more formal communication networks, and the leadership pattern is democratic. Based on the theory of human relations school, the communication between the leaders and the officers of Satpol PP is more humane approach based persuasive communication and interpersonal communication.